Peningkatan Kemampuan Membaca Kritis Melalui Model Problem Based Learning di Kelas V SD - Linda Panjaitan; Suci Perwita Sari (PT. Intelek Cendikiawan Nusantara, 2026)
This study aims to improve students' critical reading skills through the implementation of the Problem Based Learning model in Indonesian language learning for fifth-grade elementary school students. Critical reading is an essential skill that enables students to understand, analyze, and evaluate information from texts effectively. However, many students still experience difficulties in comprehending reading materials critically due to the limited use of innovative and student-centered learning strategies. This research employed Classroom Action Research (CAR) consisting of two cycles, namely planning, action, observation, and reflection. The participants of this study were fifth-grade students in an elementary school. Data were collected through observation, reading tests, and documentation to measure students' progress in critical reading skills. The results of the study showed that the implementation of the Problem Based Learning model significantly improved students' critical reading abilities. Students became more active in analyzing texts, identifying main ideas, asking questions, and expressing their opinions during classroom discussions. In addition, the learning outcomes increased in each cycle, indicating that students were able to understand reading materials more critically and effectively. Therefore, the Problem Based Learning model can be considered an effective learning strategy to enhance students' critical reading skills in Indonesian language learning at the elementary school level. Keywords : critical reading, problem based learning, students